Sovereign debt and corporate capital structure: the evidence from selected European countries during the Global Financial and Economic Crisis - Mokhova, Natalia; Zinecker, Marek (Business: Theory and Practice, 2017)
The recent Global financial crisis and the following European debt crisis show the significance of country financial stability and its impact on the private sector. Moreover, the sovereign debt as an essential element of government macroeconomic policy influences the financial performances of the companies and their future development and growth. The capital structure and financing decisions represent one of the most significant parts of company’s financial policy and its key to financial strength. There are a lot of external factors influencing the capital structure; however, due to the European debt crisis the aim of this study is to indicate the influence of sovereign debt on capital structure of the private held companies in different European countries. This study examines the evidence from European developed countries and emerging markets for the period 2005–2012, in order to compare the level of its impact on the capital structure according to the countries’ specifics. We find that after Global Financial Crisis the sovereign debt has tendency to increase in all investigated countries. Greece and Italy have the highest level of debt and it exceeds their Gross Domestic Product (GDP). In addition to that, the Czech Republic has the lowest level of sovereign debt to GDP, but at the same time the corporate capital structure exceeds 100%. The sovereign debt levels are strongly and statistically significantly correlated with each other, however, Hungarian debt has weaker relation with other countries. The findings also show the integration and interdependence of European countries. Moreover, Hungarian, Czech and German private sectors are the most depended on the level of sovereign debt.